2016
DOI: 10.3102/0013189x16633182
|View full text |Cite
|
Sign up to set email alerts
|

Science Achievement Gaps Begin Very Early, Persist, and Are Largely Explained by Modifiable Factors

Abstract: We examined the age of onset, over-time dynamics, and mechanisms underlying science achievement gaps in U.S. elementary and middle schools. To do so, we estimated multilevel growth models that included as predictors children’s own general knowledge, reading and mathematics achievement, behavioral self-regulation, sociodemographics, other child- and family-level characteristics (e.g., parenting quality), and school-level characteristics (e.g., racial, ethnic, and economic composition; school academic climate). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
240
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(293 citation statements)
references
References 87 publications
11
240
1
10
Order By: Relevance
“…The Hispanic-White gap and Asian-White gap are both smaller than the Black-White gap and decrease as students age. The female-male gap is slightly less than one-quarter of a standard deviation (Kohlhaas et al, 2010;Morgan et al, 2016;Quinn & Cooc, 2015).…”
mentioning
confidence: 97%
“…The Hispanic-White gap and Asian-White gap are both smaller than the Black-White gap and decrease as students age. The female-male gap is slightly less than one-quarter of a standard deviation (Kohlhaas et al, 2010;Morgan et al, 2016;Quinn & Cooc, 2015).…”
mentioning
confidence: 97%
“…They also mentioned that science education expanded experiential background for students who had limited experiences. Increased use of inquiry and problem-solving skills helped students with disabilities to survive with scientific literacy and enabled them to discover and manage information (Morgan, Farkas, Hillemeier, Maczuga, 2016). Sharma.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Morgan, Farkas, Hillemeier & Maczuga (2016) quote successful application of constructivist approaches to students of school age. Inquiry oriented teaching is recommended in science teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified large science achievement gaps at the end of 8th grade between white and racial/ethnic minority children, and between children from higher-and lower-income families. These achievement gaps begin very early in the educational career span (Morgan, Farkas, Hillemeier, & Maczuga, 2016). Thus, early exposure to, positive attitudes toward, and achievement in math and science are important factors in a student's declaration of a STEM major (Crisp, Nora, & Taggart, 2009).…”
Section: ⅵ Implicationsmentioning
confidence: 99%
“…A relatively low percentage of youth from poor households and/or minority populations are successful in their pursuit of STEM-related careers (Babco, 2003). Issues of disparity in equity and access in the STEM pipeline among minority and/or low-income students (e.g., American Indian, African American, and Hispanic youth) are the most prevalent challenges for improving US STEM education (e.g., Morgan, Farkas, Hillemeier, & Maczuga, 2016). It is critical for these populations to have more opportunities, including informal learning opportunities, to address their underachievement and underrepresentation in STEM and STEM-related careers (e.g., Crisp, Nora, & Taggart, 2009).…”
mentioning
confidence: 99%